Customer Satisfaction in Mediation the Influence of Service Quality and Customer Loyalty - Basrowi; Juhary, Ali (2023)
This study attempts to analyze the effect of service quality on customer satisfaction and its implications for customer loyalty. The research approach is correlational. The data is obtained by using a survey method to customers who have been customers for at least one year with a total of 168 people. The research was conducted in Jakarta. The results showed that there was a significant influence between service quality and customer satisfaction. Service quality also affects customer loyalty. Customer satisfaction is also significant to customer loyalty. The novelty of this research lies in the effectiveness of the customer satisfaction variable in mediating the effect of service quality on customer loyalty. Banking managers who want to increase customer loyalty should be able to improve service quality first and then increase customer satisfaction.